Risk stratification in acute myocardial Iischaemia: Potential use of a rapid bedside Troponin T assay - Goh, Emily M.L.; Chow, S.K.; Lang, C.C. (Faculty of Medicine, University of Malaya, 2002)
This study is to examine the use of a Rapid Troponin T test in patients attending the Emergency Room with complaints of chest pain. The results show a strong correlation between time to positive developmentaf the Rapid Trapanin T lest to ELISA Trapanin T. These results indicate the use of a simple to perform bedside assay of Rapid Trapanin T may be used in early risk stratification of patients presenting wilh acute coronary syndromes.